REPRESENTATION OF THE CONFLICT OF THE WORKING CLASS AND THE SLAUGHTER CLASS: ROLAND BARTHES' SEMIOTICS ANALYSIS IN MOVIE "TURAH" - Syahrial Agung Kurniaji; Dyva Clareta (JOSAR (Journal of Students Academic Research), 2022)
The film Turah describes a situation that exists in today's society. In the film, Turah explains the facts about social inequality in remote parts of Indonesia. Due to socio-economic disparities, social conflicts are unavoidable. This social inequality results in injustice and position in society. The striking difference is in the financial ability and social status of the people living in certain neighborhoods. This form of social inequality makes it difficult for the lower class to get access to development outcomes to education.